Gender and Educational Differences in Perception of Domestic Violence Against Women Among Libyan Migrants in Manchester - El Abani, Suaad (Journal of interpersonal violence, 2021)
Domestic violence against women (DVAW) is a worldwide phenomenon and refers to any act committed against women that results in physical and psychological harm, and coercion, loss of liberty, and deprivation. There is a dearth of research and information about the extent and prevalence of domestic violence among Libyan communities. The aim of the study was to explore community knowledge of, and attitudes toward, DVAW and to improve our understanding of the factors that influence knowledge, attitudes, and responses, particularly educational and gender differences. Using snowball sampling, we analyzed 20 semistructured interviews with Libyans living in Manchester, United Kingdom. We found gender and education-influenced participants’ perception of DVAW. Men in general did not recognize DVAW as a serious social problem; noticeably, they saw it as a personal and family issue. Knowing attitudes toward DVAW is necessary for government and communities’ prevention policies as attitudes influence perpetration of DVAW.